RELATIONSHIP BETWEEN DISTRIBUTION OF NURSING SERVICE SCHEDULES AND NURSE JOB SATISFACTION IN THE INPATIENT ROOM AT RSUD PARIAMAN REGENCY - KASMORA, DEPERMAN; AMELIATI, SRI; SYAHRUL (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2025)
The division of duty schedules in inpatient rooms can improve the performance or satisfaction of nurses who carry them out. Job satisfaction is an important aspect that influences the performance of nurses in providing health services. Nurse job satisfaction is influenced by various factors, one of which is the division of duty schedules. This study aims to determine the relationship between the division of duty schedules and the job satisfaction of nurses in the inpatient ward of Pariaman Hospital. The method used is quantitative with a correlation design and a cross-sectional approach. This study was conducted in nine wards at Pariaman Hospital in July 2024. With a sample size of all nurses on duty in the hospital's inpatient ward. The results of the study were analyzed univariately and bivariately. Sampling was carried out using the quota sampling technique with a sample size of 84 nurses from 9 inpatient wards. Data were collected through questionnaires and analyzed using the chi-square test. The results showed that the majority of respondents had a balanced and agreed upon division of duty schedules, namely 50 nurses (59.5%) and were satisfied with their work, namely 58 nurses (69.0%). There is a significant relationship between the division of work schedules and nurse job satisfaction (p-value = 0.003 <α = 0.05). Suggestion, it is expected that hospitals can implement good management such as the division of work schedules so that the performance given by nurses can be good.